Social-Engaged Art in Indonesia: Many in One, Nurturing Diversity & Inclusion - Ika Yuliana; Dominique Lämmli (Institut Seni Indonesia Yogyakarta, 2022)
This research describes three socially engaged art practices of three collectives, Gubuak Kopi (Solok, West Sumatera), Festival Film Bahari (Cirebon, West Java) and Forum Sudut Pandang (Palu, Central Sulawesi), which were located in rural-urban area in Indonesia. The practices of these collectives that are established after 2010 were then read along the concept of Bhinneka Tunggal Ika. This research method is guided by the question: How did “many, but one” emerge in the practice of social arts and who benefits from it? The narratives were built by centralizing the perspectives of art practitioners on their motivations and aims, instead of analyzing certain case studies. The method of this paper is interview and desk review. Based on the research observations, the researchers try to provide a perspective on how cultural promotion programs have an impact on community movements outside the big cities. Seni Berpenampilan Sosial di Indonesia: Ragam dalam Satu, Memelihara Kebhinekaan & Inklusi. Penelitian ini mendeskripsikan tiga praktik seni yang terlibat secara sosial dari tiga kolektif yakni Gubuak Kopi (Solok, Sumatera Barat), Festival Film Bahari (Cirebon, Jawa Barat) and Forum Sudut Pandang (Palu, Sulawesi Tengah) yang berada di daerah rural-urban di Indonesia. Tiga praktik dari kolektif yang muncul setelah 2010 ini kemudian dibaca dalam kaitannya dengan konsep Bhinneka Tunggal Ika. Penelitian ini dipandu dengan pertanyaan: bagaimana “banyak namun satu” muncul dalam praktik seni yang terlibat secara sosial di Indonesia, dan siapa yang diuntungkan oleh praktik ini? Narasi dibangun dengan memusatkan perhatian pada perspektif praktisi seni atas motivasi dan tujuan berkaryanya, alih-alih menganalisis studi kasus tertentu. Metode penelitian yang diterapkan adalah wawancara dan studi pustaka. Berdasarkan hasil observasi, peneliti menawarkan pandangan akan bagaimana program pemajuan kebudayaan memberikan pengaruh pada pergerakan komunitas di luar kota-kota besar.